Animals as covictims and more-than-property: the inclusion of companion animals in protection order statutes at the state level in the United States - Fitzgerald, Amy J. (Violence and victims, 2025)
This article analyzes statutes in 37 U.S. states and Washington, DC amended to include companion animals in definitions of domestic violence and to enable their inclusion in protection orders (POs). The findings indicate that while the inclusion of animal abuse in definitions of domestic violence tends to frame their maltreatment in anthropocentric terms—as a vehicle for harming people—the language and consequences of their inclusion in some PO statutes position them as more-than-property, that is, more as subjects than objects. The analysis documents a temporal trend toward offering greater protections over time, greater bipartisan support for the amendments, and a shift from animals-as-property toward sociolegal recognition of their social membership and the ways their well-being is interconnected with that of the people who care for them.